Dinamika Penegakan Hukum di Indonesia: Antara Kepastian Prosedural dan Keadilan Substansif - Beni Arbi Batubara (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Law enforcement in Indonesia continues to face challenges in balancing procedural legal certainty and substantive justice. A predominantly legalistic approach often produces decisions that are legally valid but do not fully reflect society's sense of justice. This study analyzes the relationship between procedural legal certainty and substantive justice and examines the role of progressive law and restorative justice in promoting fair law enforcement. The research employs a normative legal method using statutory, conceptual, and case approaches. Legal materials were collected through library research, including legislation, legal doctrines, scholarly articles, and official documents, and analyzed qualitatively using deductive legal reasoning. The findings show that procedural legal certainty and substantive justice are complementary principles. Progressive law functions as an interpretative paradigm, while restorative justice serves as an implementation mechanism that integrates legal certainty, justice, and utility. This study proposes a conceptual harmonization model that positions legal certainty as the normative foundation, progressive law as the interpretative paradigm, restorative justice as the dispute resolution mechanism, and substantive justice as the ultimate objective of law enforcement. The model is expected to guide policymakers and law enforcement agencies in developing a more adaptive, humane, and just legal system.